n-Butyldichlorido{4-cyclohexyl-1-[phenyl(2-pyridyl-kappa N)methylene]thiosemicarbazidato-kappa N-2(1),S}tin(IV) chloroform monosolvate - Abu Affan, M.; Salam, M.A.; Farina, Y.; Ng, S.W. (International Union of Crystallography, 2010)
The monodeprotonated Schiff base ligand in the title compound, [Sn(C4H9)(C19H21N4S)Cl-2]center dot CHCl3, N,N',S-chelates to the Sn atom, which is six-coordinated in an octahedral environment. The three coordinating atoms along with the butyl C atom comprise a square plane, above and below which are positioned the Cl atoms. The amino group is a hydrogen-bond donor to a Cl atom of an adjacent molecule, the hydrogen bond giving rise to a helical chain propagating in [010]. The Cl and H atoms of the chloroform molecule are disordered over two positions in an 0.67: 0.33 ratio.